2012
DOI: 10.1186/1749-799x-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the stress distribution in the distal femur between patellofemoral joint replacement and total knee replacement: a finite element study

Abstract: BackgroundPatellofemoral joint replacement is a successful treatment option for isolated patellofemoral osteoarthritis. However, results of later conversion to total knee replacement may be compromised by periprosthetic bone loss. Previous clinical studies have demonstrated a decrease in distal femoral bone mineral density after patellofemoral joint replacement. It is unclear whether this is due to periprosthetic stress shielding. The main objective of the current study was to evaluate the stress shielding eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In addition to the failures of early-generation implants, a relatively high tendency for failures directly related to patellar maltracking has been identified (Arciero and Toomey 1988;Tauro et al 2001;Board et al 2004;van Jonbergen et al 2010). Hendrix et al (2008) performed a review of these outcomes and concluded that although many of the failures have been attributed to component malposition or soft tissue imbalance, the likelihood is that many of them were, in fact, promoted by particular design features of the trochlear components, which put the patella at risk for catching, snapping and subluxation on its proximal and lateral edges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the failures of early-generation implants, a relatively high tendency for failures directly related to patellar maltracking has been identified (Arciero and Toomey 1988;Tauro et al 2001;Board et al 2004;van Jonbergen et al 2010). Hendrix et al (2008) performed a review of these outcomes and concluded that although many of the failures have been attributed to component malposition or soft tissue imbalance, the likelihood is that many of them were, in fact, promoted by particular design features of the trochlear components, which put the patella at risk for catching, snapping and subluxation on its proximal and lateral edges.…”
Section: Discussionmentioning
confidence: 99%
“…Patellofemoral arthroplasty (PFA) is a bone conserving solution for patients with isolated PF degeneration after other surgical options have failed (Delanois et al 2008;Müller et al 2012;van Jonbergen et al 2012). This technique is mainly recommended for patients under 55 years of age with isolated anterior compartment arthrosis, allowing, if necessary, for total knee arthroplasty to be performed later (Leadbetter et al 2008;Castro et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Van Jonbergen HPW et al (26) investigated the stress distribution differences in the distal femur of patients who underwent patellofemoral joint arthroplasty and total knee arthroplasty. Patellofemoral joint arthroplasty forms a stress shield around the prosthesis, but this is less than total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Patellofemoral joint arthroplasty forms a stress shield around the prosthesis, but this is less than total knee arthroplasty. They suggested that special designs of patellofemoral prostheses may result in differences of the femoral stress shield (26).…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been shown to be advantageous for obtaining insight within interfaces that otherwise would be problematic to evaluate, namely on the knee joint. 3237…”
Section: Introductionmentioning
confidence: 99%